AN ETHNOMATHEMATICAL STUDY ON CONTEMPORARY BATIK DESIGN USING ALTERNATIVE RESISTANCE - Wan Norliza Wan Bakar,; Junaidi Awang,; Nani Hartina Ahmad,; Mohd Zaffian Zawawi, (Journal of Islamic, Social, Economics and Development, 2021)
Ethnomathematics is a study of the application of mathematical thinking intothe culture of a group of people in a specific country. It is a new field of study and hasgiven a lot of contribution to the country. In this paper, the ethnomathematics study isfocusing on motifs of contemporary batik design by using alternative resistance, which isa new resistance tool that has such as iron brush, copper cake mold, paper box, andwooden broom was invented by Mr. Junaidi Awang, the lecturer of Art and Design,UiTMCK. This new invention is purposely designed to help the poor and skillful batikworkers to do the batik design. It is qualitative research by employing the triangulationmethod to comprising observation, interview, analysis of the motifs on contemporary batikdesigns via alternative resistance. The results showed that by using an iron brush theresulting motifs are circles arranged in a tessellation. By using copper cake mold, themotifs produced are hexagons arranged in tessellation and rotation. By using a paper box,the motifs created are half square-shaped arranged in tessellation, and last but not leastby using a wooden broom, circle-shaped motifs exist arranged in tessellation. It issuggested that future research can be applied to readily available and cost-effectiverecycled materials.